The Development of MANSAE as a Learning Media of Accounts for Vocational School Student of Accounting Program - Firdausi, Devi Nur Rahmawati; Andayani, Endang Sri (Universitas Negeri Malang, 2017)
The objective of this research is to develop MANSAE (Making Accounting Newbies to Study Accounts Easily) as accounts learning media for accounting student of Vocational High School. MANSAE contains terms of accounts in Indonesian and English, normal balance of accounts, groups of accounts, classification of accounts in financial statement, and effect of service entitys financial transaction to accounts changes. This research uses Research and Development (R & D) method adapted from Borg & Gallâs. These method are needs analysis, product development, expert validation, product revision I, try-out (small scale), product revision II, and final product. . Product validation wasÂ done byÂ media expert and content expert, while try-out was done by 10th grade of Accounting in SMKN 1 Turen. MANSAE get 97,61% from media expert, 88,70% from content expert, and 95,50% from limited user. The meanÂ is 93,94%, it means that from technical side, surface features, language and grammar, subject matter, and offline material is appropriate and suitable to use as accounts learning media for accounting newbies.Keywords: media, mansae, account, account dictionary